The current state of forensic imaging – post mortem imaging - Fabrice, Dedouit; Mathilde, Ducloyer; Jamie, Elifritz; Natalie, L. Adolphi; Grace Yi-Li, Wong; Summer, Decker; Jonathan, Ford; Yanko, Kolev; Michael, Thali (Springer Nature, 2025)
Over the last few decades, forensic imaging has become an essential part of current forensic practice. The aim of this 4-part review is to provide a comprehensive overview of forensic imaging over the rst 25 years of this century. After a brief historic review, this rst part details the advantages and limitations of post-mortem imaging for the indications most frequently encountered in daily practice.